THE EFFECT OF TAX AVOIDANCE AND PROFITABILITY ON FIRM VALUE IN THE BASIC MATERIAL SECTOR DURING THE 2020-2024 PERIOD - Sri Wahyuni; Wiralestari Wiralestari; Ilham Wahyudi; Enggar Diah Puspa Arum (Yayasan Nuraini Ibrahim Mandiri, 2026)
Within the Indonesia Stock Exchange (IDX), the impact of tax avoidance along with profitability toward firm value amongst basic material businesses throughout the 2020–2024 duration is investigated by this paper. Understanding how firm value is perceived by the market based on fiscal strategies alongside operational effectiveness represents the primary focus. Annual reports provided the secondary information utilised for this quantitative method of investigation. Seventy-five distinct data points were gathered across five years after fifteen firms were chosen via a purposive sampling technique. SPSS tools were applied to carry out multiple linear regression, classical assumption checks, plus descriptive statistical processing. It is revealed that tax avoidance, represented via the Effective Tax Rate (ETR), individually impacts firm value (Tobin’s Q) notably, yielding a significance figure of 0.027. Moreover, profitability (Return on Assets) similarly displays a substantial influence, possessing a 0.035 significance level. Concurrently, firm value is meaningfully altered by both factors according to the F-test outcomes (sig. 0.008). Ten per cent of firm value fluctuations are clarified by this framework per the Adjusted R Square, whereas external variables account for the other ninety per cent. Such conclusions verify that market price assessments for basic material organisations are influenced by signals like profitability and fiscal management for those investing in this area.